2016
DOI: 10.1093/ijnp/pyw106
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Dopamine D1 Receptor on the Social Hierarchy of Rodents and Non-human Primates

Abstract: Background:Although dopamine has been suggested to play a role in mediating social behaviors of individual animals, it is not clear whether such dopamine signaling contributes to attributes of social groups such as social hierarchy.Methods:In this study, the effects of the pharmacological manipulation of dopamine D1 receptor function on the social hierarchy and behavior of group-housed mice and macaques were investigated using a battery of behavioral tests.Results:D1 receptor blockade facilitated social domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…Presence or absence of social affiliations and aggressions in every 10 seconds (1,800 frames for 30 minutes) were measured, and a number of frames in which the events were present was expressed as percentage of time out of a whole recording period that these events occupied. Social affiliations and aggressions were defined as we have previously described 56 . Inter-rater reliabilities for the rates of aggressions and social affiliations between the experimenters at off-line analysis were very high (Cohen’s kappa = 0.93, with confidence interval at 0.90–0.96), indicating reliable behavioral assessments 57 .…”
Section: Methodsmentioning
confidence: 99%
“…Presence or absence of social affiliations and aggressions in every 10 seconds (1,800 frames for 30 minutes) were measured, and a number of frames in which the events were present was expressed as percentage of time out of a whole recording period that these events occupied. Social affiliations and aggressions were defined as we have previously described 56 . Inter-rater reliabilities for the rates of aggressions and social affiliations between the experimenters at off-line analysis were very high (Cohen’s kappa = 0.93, with confidence interval at 0.90–0.96), indicating reliable behavioral assessments 57 .…”
Section: Methodsmentioning
confidence: 99%
“…Four out of 8 groups tested in Ph.1 were further subjected to a tube rank test, which is another behavioral test to examine social rank of mice, and examined its correlation between FAP. In the tube rank test, David’s score (DS), which is an index of social dominance, was calculated based on a dyadic proportion of wins and losses, as conducted in our previous studies 27 , 28 . A significant positive correlation was observed between FAP and DS (r = 0.853, p < 0.001; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In social groups of non-human primates such as macaques, as well as other wild animals, linear social hierarchy exists, and a correlation between social ranks and FAP has been reported 15 , 30 . In contrast, although presence of a linear social hierarchy in rodent social groups has been observed 27 , 28 , 31 , whether mice living in social groups also exhibit FAP had yet to be determined. In this study, we found that, similar to non-human primates, FAP correlated with social ranks is also present in mouse social groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent volume of saline (SAL) was given as a control treatment. The doses of drugs were determined based on our previous macaque studies (Yamaguchi et al 2017a , b , c ), in which we tested the D1 and D2 antagonists for the visual attention task to social vs. non-social images as well as freely moving macaques in social groups. In particular, the doses of SCH23390 and sulpiride used in this study was not only previously found effective to alter various behavior of the drug-administered macaques and visual attention to social vs. non-social images, but particularly importantly, macaques were still able to sustain gazing to the images for a fixed duration during NIRS recordings.…”
Section: Methodsmentioning
confidence: 99%